PROFIL LITERASI BIODIVERSITAS PESERTA DIDIK KELAS VII SMP NEGERI - Hastuti, Aris; Suprapto, Purwati Kuswarini; Badriah, Liah; Hernawati, Diana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Biodiversity, as a vital component of ecosystem sustainability, is under significant pressure due to pollution, rapid urbanization, and climate change. This global issue also impacts local awareness, including among students at SMP Negeri Satu Atap 1 Kalipucang. This study aims to analyze the biodiversity literacy profile of seventh-grade students at the school. A descriptive quantitative method was used, with a multiple-choice test consisting of 20 items measuring 10 indicators of biodiversity literacy, including conservation and species importance, biodiversity benefits, biodiversity protection, sustainable biodiversity, biodiversity ethics, conservation awareness, environmental behavior, environmental concern, environmental knowledge, and biodiversity knowledge. The research was conducted in October 2024 with a sample of 36 students. The results showed that the average biodiversity literacy score of students was in the